Modelling a whole building stock: domestic, non-domestic and mixed use. Issue 2 (17th February 2019) - Evans, Stephen; Liddiard, Rob; Steadman, Philip
ABSTRACT: Work on energy use in buildings – in university research, professional practice and government – has tended to draw a broad distinction between 'the domestic stock' and 'the non-domestic stock'. A further tendency has been to focus attention on types of non-domestic buildings devoted to single uses ( e.g. offices, shops or hospitals). This paper reports an empirical research programme in which the complete building stock in large areas of England and Wales is comprehensively represented in great detail, using a new method and model called 3DStock. The model breaks down activities by floor level and within each floor of every building. The results show that the extent of mixing of uses is much greater than has previously been acknowledged, especially towards the centres and in the older parts of towns and cities. These mixed-activity buildings are sometimes relatively simple combinations of domestic and non-domestic, e.g. urban retail with flats above, while others are complex mixtures of different non-domestic activities. The model can be used to investigate how these complex relationships influence energy use. It is argued that, at the larger scale, explicit account needs to be taken of the mixing of uses in future stock models for research and policy-making.